Peningkatan Strategi Sistem Informasi pada Apotek Kita Sehat Menggunakan Pendekatan Metode VRIO dan SWOT - Audy Cahya Bezita (JOURNAL SAINS STUDENT RESEARCH, 2026)
Pharmacies serve as essential pharmaceutical service facilities within the healthcare system, primarily responsible for drug distribution and community health support. This study aims to formulate an information system improvement strategy for Apotek Kita Sehat by integrating the VRIO (Value, Rarity, Imitability, Organization) and SWOT (Strengths, Weaknesses, Opportunities, Threats) frameworks. This method uses descriptive qualitative research techniques by collecting data in the form of interviews, observations, and documentation studies. Findings indicate that the current information system at Apotek Kita Sehat holds strategic value in enhancing operational effectiveness, particularly in administrative processes and drug inventory management. Furthermore, SWOT analysis yields alternative strategies that prioritize leveraging internal strengths to address external threats and market dynamics. The results of the analysis conducted at Apotek Kita Sehat are expected to inform strategic decision-making regarding the development of a more integrated and sustainable information system.